THU0204 Lumbar interspinous bursitis in active polymyalgia rheumatica. (23rd January 2014) - Salvarani, C.; Barozzi, L.; Catanoso, M.G.; Boiardi, L.; Pipitone, N.; Macchioni, P.; Pazzola, G.; Bajocchi, G.; Addimanda, O.; Muratore, F.
Abstract : Objectives: To evaluate the inflammatory involvement of lumbar interspinous bursitis in patients with polymyalgia rheumatica (PMR) using magnetic resonance imaging (MRI). Methods: Ten consecutive, untreated new patients with PMR and pain in the shoulder and pelvic girdles were investigated. Seven patients with spondyloarthritis (4 with psoriatic spondyloarthrits, one with entheropatic spondyloarthritis, and 2 with primary ankylosing spondylitis), 2 patients with spine osteoarthritis, and 2 patients with rheumatoid arthritis with lumbar pain served as controls. MRI of lumbar spine was performed in all 10 PMR case patients and in 11 control patients. Nine patients (5 PMR case patients and 4 control patients) also had MRI of the dorsal spine. Results: MRI evidence of interspinous lumbar bursitis was found in 9/10 patients with PMR and in 5 control patients. A moderate to marked (grade≥2 on a semiquantitative 0-3 scale) lumbar bursitis occurred significantly more frequently in patients with PMR than in control patients (60% compared to 9%, p=0.024). In most of the patients and controls with lumbar bursitis the involvement was found at L3-L5 lumbar interspaces, only 2 patients had a more extended involvement (one case patient showed L1-L5 bursitis, and one control patient L2-L4 bursitis). No evidence of interspinous bursitis was showed at MRI of dorsal spine in case patients and controls. Conclusions: Inflammation of lumbar bursae may be responsible for the low back pain reported by patients with PMR and hip girdle involvement. The prominent inflammatory involvement of cervical and lumbar bursae supports the hypothesis that PMR may be a disorder affecting predominantly extra-articular synovial structures, in particular of bursae. Disclosure of Interest: None Declared